Menyunting Kalimat Efektif dari Aspek Kehematan pada Berita Daring Tribunnews Tahun 2022 - Ananta Muhammad Fiqi; Afifah Dijah Lestari; Fikri Badrussalam; Irwan Siagian (Journal on Education, 2023)
A sentence can be said to be a communication tool if it can convey an idea to the reader or listener. To achieve this goal, a sentence must be written effectively. Effective sentences are sentences that can clearly describe the purpose or idea to be conveyed to the reader or listener. Thus, the use of effective sentences is very helpful for readers or listeners so as not to misjudge the writing presented and the intention or idea is conveyed properly without re-reading or guessing the essence of a problem. The use of effective sentences is commonly found in argumentation essays. In news texts, there is a lot of ineffective use of sentences which results in the writer's ideas not being conveyed properly. From the brief description above, what will be the focus of the research is the use of effective sentences in the aspect of austerity in the news script of tribunNews.